Entrepreneurship in K-12 Public Education - Hill, Paul T. (Senate Hall, 2004)
The thesis of this paper is that American public education is sorely hurt by false certainty, and that greater openness to entrepreneurship could lead to more adaptable and effective schools. Educators like to say 'we know how to educate every child to high standards' but they then line up into opposing camps that struggle for control of schools via regulation. The keys to improvement in a field with technical uncertainty are provider discretion and performance accountability. If public education is to be more effective, especially for children who are not well served now, it must become open to entrepreneurship in four areas: providing support services, managing human resources, delivering complete courses, and operating whole schools.
Keywords: performance|accountability|privatization|entrepreneurship|regulation